Dexmedetomidine vs. propofol on arrhythmia in cardiac surgery: a meta-analysis of randomized controlled trials - Peng, Juan; Wu, Yifan; Li, Lin; Xia, Panpan; Yu, Peng; Zhang, Jing; Liu, Xiao (Frontiers in Cardiovascular Medicine, 2024)
Background: Dexmedetomidine (DEX) and propofol are popular anesthetics, but it remains unknown whether DEX reduces the incidence of arrhythmias compared with propofol after cardiac surgery. Methods: We performed a comprehensive search for RCTs (Randomized Controlled Trials) that compared the incidence of arrhythmias between DEX and propofol in adults who had undergone cardiac surgery across three databases (PubMed, Embase, the Cochrane Library), and ClinicalTrials.gov up to October 3, 2023. The primary outcome was ventricular arrhythmias, the secondary outcomes were bradycardia and atrial fibrillation (AF). Results: Our analysis included 7 RCTs with 1,004 patients (mean age: 64.37, male: 71.11%) undergoing cardiac surgery, and the incidence of in-hospital arrhythmia was 22.01% (ventricular arrhythmias 2.75%, bradycardia 3.33%, AF 18.63%). Perioperative or postoperative use of DEX reduced the incidence of in-hospital ventricular arrhythmias (Odds Ratio [OR] 0.14, 95% Confidence Interval [CI] 0.03-0.66), but increased the risk of in-hospital bradycardia (OR 2.88, 95% CI 1.02-8.17) compared with propofol. The trial sequence analysis verified the adequacy of sample size and robustness of the ventricular arrhythmias and bradycardia. There was no significant reduced incidence of the use of DEX in the incidence of AF (OR 0.69, 95% CI 0.36-1.29). The GRADE assessment indicated a high certainty for ventricular arrhythmias and bradycardia and a moderate certainty for AF. Conclusions: Our findings suggested the use of DEX reduces in-hospital ventricular arrhythmias but increases bradycardia incidence compared to propofol in adult patients undergoing cardiac surgery. Further studies are needed to assess the impact of dexmedetomidine on atrial fibrillation compared to propofol.